Foraging activity of the snail kite, Rostrhamus sociabilis (Aves: Accipitridae) in wetlands of southern Brazil - FB Bergmann; HLC Amaral; DP Pinto; CC Chivittz; AM Tozetti (Brazilian Journal of Biology)
The snail kite (Rostrhamus sociabilis) is widely distributed in the American continent. Its specialised diet consists mostly of the gastropod mollusk Pomacea sp and its foraging strategy probably varies depending on the season, prey availability, and climate factors, which can be reflected in its semi-nomad behaviour. This study was aimed at examining the hunting strategy of the snail kite, and its association with climate factors and habitat heterogeneity. Direct observations of birds between January 2010 and March 2011 in southernmost Brazil revealed that hunting was still the predominant foraging strategy (79% of records) to capture mollusks. Despite morphological specialisations to extract mollusks from the shells, the handling time (average = 92.4 s) was twice as much the time between prey search and capture (average = 55 s). The increase in the number of mollusks ingested apparently occurs when the resting time on perches or any other substrates near the hunting sites decreases between successive unsuccessful attempts. The correlation between the number of consumed preys and the climatic variables examined was low. Regarding habitat heterogeneity, our findings suggest that birds forage preferentially in marshes with low vegetation, which may increase the access to mollusks. The hunting efficiency of the snail kite was high (76 % successful attempts) compared to those of other birds of prey.